Maternal and Neonatal Outcomes in Late Preterm vs. Full-Term Deliveries: A Comparative Cohort Study - Shah, Dhrumil; Saini, Paramjeet (International Journal of Medical Research, 2024)
Introduction: Late preterm infants, born between 34 0/7 and 36 6/7 weeks of gestation, are often regarded as functionally similar to term infants. However, growing evidence suggests that these neonates experience higher risks of morbidity and mortality compared to term infants. This study aimed to compare maternal and neonatal outcomes of late preterm deliveries with those of full-term deliveries to highlight the clinical challenges and complications associated with late preterm births. Methodology: This prospective cohort study included 312 pregnant women, with 104 delivering at late preterm and 208 at full term. Data were collected on maternal characteristics, labour onset, delivery mode, neonatal outcomes, and complications. Statistical analysis was performed to identify significant differences between the two groups. Results: Late preterm infants demonstrated significantly lower birth weights (mean 1734 g vs. 2348 g) and higher rates of NICU admission (64.4% vs. 16.8%). Neonatal morbidities, such as respiratory distress (36.5% vs. 12.5%) and jaundice (26.9% vs. 9.6%), were more frequent in the late preterm group. Maternal outcomes varied, with higher rates of labour induction (70.2% vs. 38.5%) and caesarean sections (42.3% vs. 28.4%) in the late preterm group. Neonatal mortality was also higher in late preterm infants (8.7% vs. 1.9%). Conclusion: Late preterm births are associated with increased neonatal and maternal complications compared to full-term deliveries. These findings underscore the need for specialized care and monitoring for late preterm pregnancies to improve maternal and neonatal health outcomes.